2013
DOI: 10.5152/jtgga.2013.05
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic endometrial thickness measurement is predictive for treatment response in simple endometrial hyperplasia without atypia

Abstract: Objective: We sought to determine the predictors of treatment response in simple endometrial hyperplasia without atypia. Material and Methods:We prospectively treated 67 women with simple endometrial hyperplasia without atypia who were administered cyclic oral medroxyprogesterone acetate 10 mg/day for 12 days of luteal phase for 3 months and underwent control endometrial sampling after treatment. All subjects were evaluated in terms of age, gravidity, parity, body mass index (BMI), menstrual cycle, endometrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
0
10
0
4
Order By: Relevance
“…Many studies investigating BMI reported that obesity was associated with failure to achieve disease regression and increased recurrence (105,(127)(128)(129)(130) . However, a recent study of Japanese women reported that lower BMI was associated with increased recurrence (131) , whilst numerous studies have reported no association between BMI and outcome (132)(133)(134)(135)(136)(137) . The association between age or menopause status and outcome are also conflicting, with two studies reporting younger age or premenopausal status were associated with disease regression or reduced recurrence (127,132) , whilst another reported younger age was associated with increased recurrence (136) .…”
Section: Systematic Review Of Biomarkers Of Progestin Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies investigating BMI reported that obesity was associated with failure to achieve disease regression and increased recurrence (105,(127)(128)(129)(130) . However, a recent study of Japanese women reported that lower BMI was associated with increased recurrence (131) , whilst numerous studies have reported no association between BMI and outcome (132)(133)(134)(135)(136)(137) . The association between age or menopause status and outcome are also conflicting, with two studies reporting younger age or premenopausal status were associated with disease regression or reduced recurrence (127,132) , whilst another reported younger age was associated with increased recurrence (136) .…”
Section: Systematic Review Of Biomarkers Of Progestin Responsementioning
confidence: 99%
“…Multiple studies have reported no association between age or menopause status and outcome (105, 128-131, 133-135, 137) . A thinner endometrium has been associated with disease regression or reduced recurrence in one study each of women with endometrial hyperplasia (128,134) . Diabetes has been associated with increased recurrence in one study (128) but not in other studies (127,129,130,137) .…”
Section: Systematic Review Of Biomarkers Of Progestin Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In patients with PCOS, unfortunately, there are no clear clinical guidelines to determine when an endometrial biopsy should be performed to exclude endometrial disease. 33 Physicians perform the biopsy for the following clinical indications: sonographic endometrial stripe thickness of 9, 7, or 9.35 mm patient history of irregular bleeding or >12 months of amenorrhea. 34,35 In order better to understand the distribution of endometrial lesions in infertility patients with PCOS before undergoing IVF, we investigated the endometrial histology of each women with PCOS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Как указано в работе Е. Ozkaya и др. [10], толщина эндометрия свы-ше 16,5 мм значимо связана с риском рециди-ва: отношение шансов (ОШ) 4,4 (95% ДИ 1,2-17,4; р < 0,03). В нашем исследовании М-эхо свыше 15 мм наблюдалось у 24 (27,3%) жен-щин группы Рц и 25 (13,3%) группы К (ОШ 2,45; 95% ДИ 0,57-4,32; р < 0,005), а М-эхо свыше 16 мм -у 19 (21,6%) и 23 (12,2%) соответственно (ОШ 1,98; 95% ДИ 0,02-3,93; р < 0,04).…”
Section: результаты исследования и их обсуждениеunclassified